Gambaran Kualitas Hidup dan Penggunaan Alat Bantu Dengar Anak Tuna Rungu SLBN II Banjarmasin - Kurniadi, Melody Audria (PERHATI-KL, 2023)
Background: Hearing loss affects a person’s ability to communicate actively. In addition to socialbarriers, non-interactive communication can affect a person’s emotional state. Early intervention at achild’s age is very important to note. Purpose: To provide an overview of the quality of life (QoL) of deafchildren socially and emotionally, and to assess the use of hearing aids (HA) in their daily lives. Method:Conducted using a cross-sectional method on 37 students aged 11-18 years, at the Government SpecialSchool II Banjarmasin. The research media used was a Strength and Difficulties questionnaire. The datawas then processed using SPSS. Subjects were 19 male and 18 female, with the highest number being 13years of age. Only 1 participant had anatomical abnormalities in the ear canal. All students had hearingloss and did not know the cause of hearing loss. Result: As many as 50% of participants experiencedabnormalities in behaviour, 40% were borderline, and only 10% were normal. The relationship problemsin peer groups sub-scale experienced the most disruption. Almost all participants (97%) of the study didnot use their HA due to damaged (13%), or being left at home (65%). Conclusion: All children usedsign language as a way of communication, and never had speech therapy. Almost all deaf children hadbehavioural disorders. Most participants (97%) did not wear their HA. This was one of the factors thatcaused the quality of life of children with hearing impairment to decline.Keywords: hearing loss, deaf, child, behavioural disorder, hearing aid, quality of life